All-ceramic or metal-ceramic tooth-supported fixed dental prostheses (FDPs)? A systematic review of the survival and complication rates. Part I: Single crowns (SCs). Issue 6 (June 2015) - Sailer, Irena; Makarov, Nikolay Alexandrovich; Thoma, Daniel Stefan; Zwahlen, Marcel; Pjetursson, Bjarni Elvar
Abstract: Objective: To assess the 5-year survival of metal-ceramic and all-ceramic tooth-supported single crowns (SCs) and to describe the incidence of biological, technical and esthetic complications. Methods: Medline (PubMed), Embase, Cochrane Central Register of Controlled Trials (CENTRAL) searches (2006–2013) were performed for clinical studies focusing on tooth-supported fixed dental prostheses (FDPs) with a mean follow-up of at least 3 years. This was complimented by an additional hand search and the inclusion of 34 studies from a previous systematic review[1, 2] . Survival and complication rates were analyzed using robust Poisson's regression models to obtain summary estimates of 5-year proportions. Results: Sixty-seven studies reporting on 4663 metal-ceramic and 9434 all-ceramic SCs fulfilled the inclusion criteria. Seventeen studies reported on metal-ceramic crowns, and 54 studies reported on all-ceramic crowns. Meta-analysis of the included studies indicated an estimated survival rate of metal-ceramic SCs of 94.7% (95% CI: 94.1–96.9%) after 5 years. This was similar to the estimated 5-year survival rate of leucit or lithium-disilicate reinforced glass ceramic SCs (96.6%; 95% CI: 94.9–96.7%), of glass infiltrated alumina SCs (94.6%; 95% CI: 92.7–96%) and densely sintered alumina and zirconia SCs (96%; 95% CI: 93.8–97.5%; 92.1%; 95% CI: 82.8–95.6%). In contrast, the 5-year survival rates of feldspathic/silica-based ceramic crowns were lower ( p  < 0.001). When the outcomes in anterior and posterior regions were compared feldspathic/silica-based ceramic and zirconia crowns exhibited significantly lower survival rates in the posterior region ( p  < 0.0001), the other crown types performed similarly. Densely sintered zirconia SCs were more frequently lost due to veneering ceramic fractures than metal-ceramic SCs ( p  < 0.001), and had significantly more loss of retention ( p  < 0.001). In total higher 5 year rates of framework fracture were reported for the all-ceramic SCs than for metal-ceramic SCs. Conclusions: Survival rates of most types of all-ceramic SCs were similar to those reported for metal-ceramic SCs, both in anterior and posterior regions. Weaker feldspathic/silica-based ceramics should be limited to applications in the anterior region. Zirconia-based SCs should not be considered as primary option due to their high incidence of technical problems.